When a segmentectomy is not a segmentectomy: Quality assurance audit and evaluation of required elements for an anatomic segmentectomy - Weiss, Kathleen D.; Deeb, Ashley L.; Wee, Jon O.; Swanson, Scott J.; Bueno, Raphael; Jaklitsch, Michael T.; Rochefort, Matthew M. (The Journal of thoracic and cardiovascular surgery, 2023)
The advent of lung cancer screening and detection of smaller nodules amplifies the need to clarify the oncological quality of sublobar resections. Furthermore, studies comparing sublobar resections to lobectomies offer conflicting conclusions. We hypothesize that this is driven, in part, by inconsistency in reporting; that is, variable interpretation of what constitutes an operative segment. Without an established standard, 2 very different operations may be reported as segmental resections, leaving the data on sublobar approaches subject to interpretative variability. A retrospective audit was performed on all segmental resections from May 2016 to December 2019 at Brigham and Women's Hospital. Pathology and operative reports were reviewed, with particular attention to the dissection of the component artery, vein, and bronchus. Resections with dissection and division of at least 1 major vascular structure (the segmental artery or vein), as well as the segmental bronchus, met operative criteria for anatomic segmentectomy. Surgical quality metrics were compared between the 2 groups. There were 271 segmental resections: 219 (80.8%) were anatomic segmentectomies and 52 (19.2%) were nonanatomic segmentectomies. For the entire cohort, nonanatomic segmentectomies had smaller margins (1.0 vs 1.5 cm; P = .02), fewer lymph nodes (2.0 vs 6.0; P < .001), and fewer mediastinal lymph node stations sampled (1.0 vs 2.0; P < .001). Similarly, there were smaller margins (1.5 vs 1.8 cm; P = .03), fewer lymph nodes (2.0 vs 6.0; P < .001), and fewer mediastinal lymph node stations sampled (1.0 vs 2.0; P < .001) in nonanatomic segmentectomies for non–small cell lung cancer. Nearly 20% of reported segmentectomies may not meet criteria for true segmental resection. Therefore, prior studies may need further scrutiny to clarify outcomes and results. Establishing a professional standard may help mitigate ambiguity in published data on this subject. Graphical representation of the conclusion that if 20% of reported segmentectomies are nonanatomic, then professional societal standards are needed to ensure that all patients receive the same quality of care. [Display omitted]